Imaginaries of a ‘Europe of the regions’ (Transactions of the Association of European Schools of Planning, 2019)
“I have not come here this evening to talk to you about a utopia; no, I am here to talk to you about an adventure ...: the federating of Europe.”These are the words of Denis de Rougemont (1948, p.1), the Swiss philosopher and scholar, given at a talk on 22nd of April 1948 at the Sorbonne, Paris. He was advocating for the cultural, historical regions to become the sub-European political units instead of nation states. I start this essay with his statement not because I necessarily agree with his views, but because he is the person who coined the term ‘Europe of the regions’ in his book The idea of Europe, which appeared in English in 1966 (de Rougemont, 1966). Donald Tusk (2016), former President of the European Union (EU), called him “a philosopher of regionalism” and “a pioneer of the EU moto of ‘unity in diversity’”. I also started this essay with de Rougemont because of his take on what constitutes Europe. In his book, he traces the history of the idea from the Greek myth of the abduction of Europa by Zeus to the 18th and 19th century federalist ideas of Napoleon and the 1960s European Community, and concludes that the search for Europe is to build Europe; that, Europe is only to be found in the process of creating it (de Rougemont, 1966). This relational perspective somewhat resonates with what I am going to discuss about ‘the region’ and a ‘Europe of the regions’.